Towards Sustainable Tourism: How the Innovative Policy Drives the Rusa Lake Development in Kampar Regency? - Erfan Fajri; Tunjung Sulaksono; Arif Rahman Hakim (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study examines public policy innovation in the development of Rusa Lake Tourism as a sustainable tourism destination in Kampar Regency, Indonesia. It focuses on policy renewal practices, the development and implementation of sustainable innovation, and the role of local government in supporting long-term tourism sustainability. The research adopts a qualitative descriptive design using a phenomenological approach, drawing on in-depth interviews with 11 purposively selected participants and complemented by field observations. Data were analyzed through thematic analysis supported by NVivo 12 Plus to systematically identify patterns related to policy innovation and collaborative governance in tourism development. Conducted over a 69-day period, the findings show that policy renewal is driven by experiential and cultural innovations, including the Danau Rusa Festival and the introduction of water-based attractions. Nevertheless, the implementation of sustainable innovation remains gradual and is constrained by fiscal limitations and institutional capacity. The local government plays a dominant role as both enabler and process manager, while collaborative governance arrangements are not yet fully institutionalized. This study contributes to tourism and public policy literature by highlighting collaborative governance as a critical foundation for sustaining tourism policy innovation and underscores the importance of formalizing multi-actor collaboration to strengthen sustainable development in nature-based tourism destinations in Indonesia.